The First Decade of Web-Based Sports Injury Surveillance: Descriptive Epidemiology of Injuries in US High School Boys' Basketball (2005-2006 Through 2013-2014) and National Collegiate Athletic Association Men's Basketball (2004-2005 Through 2013-2014) - Clifton, D. R.; Onate, J. A.; Hertel, J.; Pierpoint, L. A.; Currie, D. W.; Wasserman, E. B.; Knowles, S. B.; Dompier, T. P.; Marshall, S. W.; Comstock, R. D.; Kerr, Z. Y. (Journal of Athletic Training, 2018)
Context The advent of Web-based sports injury surveillance via programs such as the High School Reporting Information Online system and the National Collegiate Athletic Association Injury Surveillance Program has aided the acquisition of boys' and men's basketball injury data.